Examining the importance of supporting youth's basic needs in one youth leadership programme: a case study exploring programme quality. Issue 2 (3rd April 2017) - Bean, Corliss; Harlow, Meghan; Forneris, Tanya
Abstract: Researchers outline the importance of understanding features that enhance quality within youth programmes. One feature is youth's basic psychological needs support. The purpose of this study was to examine if differences existed between two leaders in delivery of one youth leadership programme related to programme quality and needs support. A mixed-methods approach was employed. Programme quality was assessed quantitatively from researchers' observations. Youth self-reported on needs support and participated in semi-structured interviews. Results indicated significant differences on programme quality with Leader 1 rating higher on safe and supportive environment than Leader 2. Youth perceived Leader 1 as more effective than Leader 2 in providing a psychologically safe environment and fostering needs support. Implications and future directions are discussed.